Penguatan Prinsip Transparansi Dalam Sentralisasi Izin Usaha Pertambangan Minerba Guna Meminimalisir Korupsi - Putri, Elsa Ardhilia; Rahayu, Ika Putri; Komaria, Lailatul; Butar Butar, Franky (Universitas Brawijaya, 2023)
Amendment to Law on Mineral and Coal Mining makes the authority to issue Mining Business Permits (IUP) shifted from local governments, including governors and regents/mayors (decentralization), to the central government (centralization). The centralization of the IUP issuance gives full authority to the central government in issuing IUP. This normative research is carried out to determine the extent to which the principle of transparency is applied after the Minerba Law 3/2020. The results show that shifting the authority of IUP issuance from the regional government to the central government does not eliminate the threat of bribery corruption as it does not strengthen the principle of transparency. Whereas the principle of transparency is the key to minimizing corruption in mining permit bribes. The solution is reforming Mineral and Coal Mining regulations and strengthening the related institutions to uphold the principle of transparency in the rezime of IUP centralization.